Review of Brand Loyalty Literature: 2001 – 2015 - Cengiz, Hakan; Akdemir-Cengiz, Hülya (Journal of Research in Marketing (ISSN: 2292-9355), 2016)
This paper examines the academic literature on brand loyalty and presents a comprehensive bibliography on the subject via classification schemes molded in the examination. With this purpose, this study scanned seven different online databases and accessed about 400 studies published between 2001 and 2015. Among these, this study examined 140 empirical research papers, the primary research topic of which is brand loyalty and classified them according to various beneficial factors. Classification schemes were formed by examining three 5-year periods (2001–2005, 2006–2010, and 2011–2015). We classified the research papers into three categories on the basis of their approaches to measuring brand loyalty: the behavioral approach, the attitudinal approach, or the multi-domain approach that combines the first two approaches. A yearly examination reveals that more studies adopted the multi-domain approach than either of the two other singular approaches. As the only study with an inclusive review of all the research studies on brand loyalty between 2001 and 2015, this study provides a comprehensive resource to marketing practitioners and researchers interested in brand loyalty to aid them in their work.